RISE: A minute with researcher: Assoc. Prof. Dr Mohd Hafiz Hanafiah / Assoc. Prof. Dr Mohd Hafiz Hanafiah - Hanafiah, Mohd Hafiz (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
A young, passionate and prominent researcher of Tourism Economics, Associate Professor Dr Mohd Hafiz Mohd Hanafiah, CHIA or fondly known as Dr Hafiz has been serving UiTM for more than a decade. He is now the Deputy Dean of Research, Industry and Linkages at Faculty of Hotel Management and Tourism, overseeing the research related businesses namely publications, grants and the likes. He is also a Certified Hotel Industry Analytics (CHIA) and a member of the Islamic Tourism Center of Malaysia's Board of Trustee.